2018
DOI: 10.1186/s13058-018-1028-5
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-B receptor increases the resistance to tamoxifen in estrogen receptor-positive breast cancer cells

Abstract: BackgroundsTamoxifen is typically used to treat patients with estrogen receptor alpha (ERα)-positive breast cancer. However, 30% of these patients gain acquired resistance to tamoxifen during or after tamoxifen treatment. As a Ras modulator, Nogo-B receptor (NgBR) is required for tumorigenesis through the signaling crosstalk with epidermal growth factor (EGF) receptor (EGFR)-mediated pathways. NgBR is highly expressed in many types of cancer cells and regulates the sensitivity of hepatocellular carcinoma to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Our previous results indicated that the hydrophobic cytosolic domain of NGBR binds farnesylated RAS ( 26 ). We previously demonstrated that NGBR is essential for RAS plasma membrane translocation in tumor cells, and NGBR overexpression recapitulates the oncogenic functions of RAS in cell transformation and tumor growth ( 26 , 33 , 61 63 ). Here, we further elucidate the roles of NGBR in regulating malignancy of proliferating hemangioma.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous results indicated that the hydrophobic cytosolic domain of NGBR binds farnesylated RAS ( 26 ). We previously demonstrated that NGBR is essential for RAS plasma membrane translocation in tumor cells, and NGBR overexpression recapitulates the oncogenic functions of RAS in cell transformation and tumor growth ( 26 , 33 , 61 63 ). Here, we further elucidate the roles of NGBR in regulating malignancy of proliferating hemangioma.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, Gao et al discovered that increased NgBR can enhance EGF-stimulated Ras activation and phosphorylation of AKT and ERK in tamoxifen-resistant breast cancer cells ( Gao et al, 2018 ). Moreover, NgBR expression is associated with non-small cell lung cancer (NSCLC) development and increases Snail 1 expression in NSCLC cells by MEK/ERK pathway activation ( Wu.et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Small interfering RNA (siRNA) is a double-stranded RNA of 20 to 25 nucleotides in length and has many important functions in biology [ 155 ]. It primarily plays a unique role in the RNA interference events which regulates gene expression in a specific manner.…”
Section: Advanced Applications Of Cs-based Nanomaterials For Drug mentioning
confidence: 99%